INTEGRATED EDUCATION AND ASSISTANCE TO OPTIMIZE THE QUALITY OF LIFE OF THE ELDERLY WITH HYPERTENSION - Vidhiastutik, Yusiana; Widyowati, Agustin; Elina, Agusta Dian (Journal of Indonesian Public Health Service, 2025)
Hypertension is one of the most common health issues experienced by the elderly worldwide, including in Indonesia. In Kepuhkembeng Village, Peterongan District, Jombang Regency, hypertension is a serious concern as it can significantly reduce the quality of life of the elderly and increase the risk of cardiovascular complications such as stroke and heart failure. This integrated education and mentoring program aims to improve the knowledge and quality of life of elderly individuals with hypertension through health education interventions, increased medication adherence, and adoption of a healthy lifestyle. The program involved 48 elderly participants and included structured health education, support through elderly health services (Posyandu Lansia), and the engagement of families and health cadres to monitor the elderly's blood pressure continuously. Through pre-test and post-test methods, evaluations showed a significant increase in the elderly’s knowledge of hypertension and its management. The average knowledge score improved from 5.6 to 8.3, and mean blood pressure readings decreased from 154/92 mmHg to 140/86 mmHg after the intervention. These results underscore the importance of integrated education and mentoring programs in managing hypertension and highlight the role of family and community in enhancing the quality of life of elderly individuals.